Preventing sepsis development in complicated urinary tract infections. Issue 1 (2nd January 2020) - Petrosillo, Nicola; Granata, Guido; Boyle, Breida; Doyle, Maeve M.; Pinchera, Biagio; Taglietti, Fabrizio
ABSTRACT: Introduction : Urinary tract infections (UTIs) are the most prevalent infections in the community and the most common reason for antimicrobial prescribing in ambulatory care. A UTI is defined as complicated when urinary tract anatomical abnormalities or urinary devices are present, when it is recurrent and when associated with immunodeficiency. Complicated UTIs (cUTIs) have a higher risk of treatment failure and often require longer antimicrobial treatment courses. cUTIs, especially those which are healthcare-associated, are often due to multidrug resistant organisms (MDROs). Areas covered : This article will review the available evidence in relation to prevention of sepsis in cUTI, evaluating the risk factors associated with sepsis development. Published articles from January 2005 to September 2019 on UTIs and sepsis prevention in complicated UTIs were identified by using MEDLINE (National Library of Medicine Bethesda MD) and by reviewing the references of retrieved articles. Expert opinion : Prevention of sepsis relies on prompt and timely diagnosis of cUTI, early identification of the causative organism, removal of obstructions and source control, proper and adequate empirical/targeted antimicrobial treatment. In particular, source control, i.e. removal of urinary obstructions, infected stents, urinary catheters, nephrostomies, and drainage of hydronephrosis/abscess, is essential for preventing the development and progression of sepsis.